Hubungan Antara Status Gizi dengan Tingkat Fleksibilitas Tubuh pada Mahasiswa Fakultas Kedokteran Unisba - Hannia Azzahra Zahlevi; Rizky Suganda Prawiradilaga; Siti Annisa Devi Trusda (Bandung Conference Series: Medical Science, 2024)
Abstract. Flexibility is the ability to move body parts through a range of motion, such as joints, tendons and tissues. A person's flexibility can be influenced by several factors, one of which can be influenced by fat accumulation which can make it difficult for a person to move flexibly. This study aims to see the relationship between nutritional status and body clotting levels in UNISBA Medical Faculty students. This research uses quantitative analytical observational research with a cross-sectional design. The sampling technique in this research used non-probability sampling with purposive sampling. The subjects of this research were 84 students with inclusion criteria including being registered as active students at the Faculty of Medicine, Bandung Islamic University for the 2022-2023 academic year and being students aged >20 years. Exclusion criteria included students with a history of injury to the lower back or hamstring muscles and students with joint deformities or a history of joint disease. Level of flexibility was measured using the sit-and-reach test and nutritional status was measured by calculating Body Mass Index and physical activity was measured using the IPAQ questionnaire. Statistical tests use the Gamma correlation test. The research results showed that there was no relationship (p=0.212, r=0.177) between nutritional status and level of welfare. Even though there is no relationship between nutritional status and the level of cold, a person still needs to have good taste to live their daily life. Abstrak. Fleksibilitas merupakan kemampuan untuk menggerakkan bagian tubuh melalui rentang gerak, seperti persendian, tendon dan jaringan. Fleksibilitas seseorang dapat dipengaruhi oleh beberapa faktor, salah satunya dapat dipengaruhi oleh penumpukan lemak yang dapat membuat seseorang sulit untuk bergerak fleksibel. Penelitian ini bertujuan untuk melihat hubungan antara status gizi dengan tingkat fleksibilitas tubuh pada mahasiswa Fakultas Kedokteran UNISBA. Penelitian ini menggunakan jenis penelitian kuantitatif analitik observasional dengan desain cross-sectional. Teknik pengambilan sampel pada penelitian ini menggunakan non-probability sampling dengan jenis purposive sampling. Subjek penelitian ini sebesar 84 mahasiswa dengan kriteria inklusi meliputi terdaftar sebagai mahasiswa aktif Fakultas Kedokteran Universitas Islam Bandung tahun ajaran 2022-2023 dan merupakan mahasiswa dengan usia >20 tahun. Kriteria eksklusi meliputi mahasiswa dengan riwayat cedera pada punggung bagian bawah atau otot hamstring dan mahasiswa dengan kelainan bentuk sendi atau riwayat penyakit sendi. Tingkat fleksibilitas diukur menggunakan sit-and-reach test dan status gizi diukur dengan menghitung Indeks Massa Tubuh. Uji statistik menggunakan uji korelasi Gamma. Hasil penelitian menunjukkan tidak terdapat hubungan (p=0,212, r=0,177) antara status gizi dengan tingkat fleksibilitas. Meskipun tidak terdapat hubungan antara status gizi dengan tingkat fleksibilitas, namun seseorang tetap harus memiliki fleksibilitas yang baik untuk menjalani kehidupan sehari-hari.